Analisis Framework, Library Front-End Populer : Bootstrap, Tailwind CSS, React, dan Vue Pada Mata Kuliah Perancangan Web Design - Harahap, Baginda; Raihan Ramadhan, Muhammad; Kurniawan, Novri; Rambe, Aripin (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2025)
Bootstrap and Tailwind CSS focus more on styling and require additional JavaScript for dynamic manipulation and form validation. Bootstrap provides visual classes that support HTML5 validation, while Tailwind CSS requires manual validation. React and Vue make form validation easier through data binding and external library support. In conclusion, React and Vue are more suitable for applications with high interactivity and dynamic needs, while Bootstrap and Tailwind CSS are more appropriate for rapid prototyping and static design. This study provides insight for developers in choosing front-end technology according to project needs. The results of the analysis show that React and Vue excel in DOM and event management because they use virtual DOM and a reactive system that facilitates the development of interactive applications.